Experimental investigation of flow around a square cylinder with very small aspect ratios. (15th October 2020) - Yang, Hanbin; Yang, Wanli; Yang, Tong; Li, Qiao
Abstract: Flow around a pile-cap of bridge is three-dimensional and complicated. When the influence of pile group and bridge pier is ignored, the current forces on the pile-cap are significantly affected by aspect ratio AR, free surface and free end. Experiments were conducted to investigate the drag force, transverse force, vertical force and flow field of a square cylinder with AR ranging from 0.033 to 1 and Re ranging from 5.4 × 10 4 to 23.1 × 10 4 . Visualization of the flow field shows that two recirculation zones generate below and behind the square cylinder respectively. The interaction of spanwise vortices generated from both sides of the square cylinder is attenuated by the free end effect. For the case with AR  = 0330., when R e = 15.1 × 10 4 ~ 23.1 × 10 4, the free surface deforms severely and air is sucked into the free end to form an air cavity, then the air cavity expands, breaks up into smaller bubbles and escapes away from the free end. The changing rules of the force coefficients of the cases with AR smaller than 0.167 are different from that with AR larger than 0.167. Highlights: Flow around a square cylinder with very small aspect ratio is investigated. Free surface deforms severely and hydraulic jumps generate when AR  = 0.033 and 15.1 × 10 4 ≤ R e ≤ 23.1 × 10 4 . Air is sucked into the free end shear layer to form an air cavity or air bubbles when AR  = 0.033 and 15.1 × 10 4 ≤ R e ≤ 23.1 × 10 4 . When 0.033 ≤ A R ≤ 0.167, C d ‾, C d r m s ‾ and C l r m s ‾ decrease with AR but C z r m s ‾ increases with AR . When 0.167 < A R ≤ 1, C d ‾, C l r m s ‾ and C z r m s ‾ increase with AR but C d r m s ‾ keeps as constant 0.13 .